Optoelectrode based on conductive fiber Fabry-Perot probe for simultaneous electrochemical and optical sensing. (December 2022) - Chang, Xinyu; Wen, Xingyue; Gao, Danheng; Luo, Meng; Teng, Pingping; Zhu, Zheng; Zhang, Jianzhong; Li, Kang; Copner, Nigel; Yang, Xinghua
Highlights: An integrated optical fiber optoelectrode based on F-P cavity functionalized by ITO is first proposed. The optoelectrode is first used to simultaneously realize the function of electrochemical working electrode and fiber sensing. The electrochemical behavior of K3 [Fe(CN)6 ] and K4 [Fe(CN)6 ] on the surface of the optoelectrode can be sensed. Abstract: In this paper, an integrated optical fiber optoelectrode based on Fabry–Perot (F-P) cavity functionalized by ITO is first proposed to simultaneously realize the function of electrochemical working electrode and the function of fiber sensing. In the experimental prototype, the redox reaction of K3 [Fe(CN)6 ] system in electrochemical reaction was token as an example. Simultaneous monitoring of the electrochemical and optical responses of the optoelectrode at different scan rates is discussed. The results show that the electrochemical behavior of K3 [Fe(CN)6 ] and K4 [Fe(CN)6 ] on the surface of the F-P-ITO optoelectrode can be successfully monitored. As the electrochemical process proceeds, local refractive index changes around the optical fiber F-P-ITO optoelectrode dominated by diffusion control will induce an obvious shift in the interference spectrum. Significantly, this novel structure of integrated F-P optoelectrode functionalized by conductive ITO based on fiber interferometer has great potentials in the fields of electrochemistry systems and biomedical applications.